Transformative learning to promote transformative evaluation of food system praxis - Dickson Otieno; Kim Niewolny; Thomas Archibald; Todd Schenk; Nicole Nunoo (Frontiers in Sustainable Food Systems, 2023)
Evaluation ideally plays an important role in determining the value and impact of community food system initiatives and movements, providing recommendations for informed decision-making, learning, and programmatic adjustments. Given that community food system work is characterized by critical praxis rooted in deconstructing dominant epistemologies and addressing social and systemic injustices—including discourses and practices from agroecology, food justice, and food sovereignty movements—simple, technical-rationalist approaches to evaluation are inadequate and inappropriate. In parallel with recent developments in critical food system work, the field of evaluation has evolved toward more critical and transformative approaches—including Culturally Responsive and Equitable Evaluation, indigenous evaluation, feminist evaluation, all generally regrouped within the framework of the transformative evaluation paradigm. At the nexus of these trends, to meet the rising demand for critical evaluative thinkers ready to grapple with the complex, dynamic, and contested questions of community food system praxis evaluation, there is a need to equip emerging evaluators with the requisite knowledge of evaluation approaches. To be ready to be critically reflective evaluators, in food system praxis and beyond, the next generation of emerging evaluators must engage fruitfully and in practically wise ways with the complex and contested aspects of critical food system work. Reflecting on the burgeoning literature on evaluator education and evaluation capacity building (ECB), and given the centrality of critical praxis and transformation in both food system work and evaluation alike, we posit that transformative learning theory has a potential role to play in preparing evaluators to meet these challenges. As such, the purpose of this conceptual paper is to highlight the intersections between critical evaluation approaches and critical food system praxis, and propose transformative learning theory as one way to help emerging evaluators prepare to meaningfully grasp and engage with the complexities manifest at this nexus of critical food evaluation praxis.